Neural-network-based model predictive control for consensus of nonlinear systems - Floriano, Bruno Rodolfo de Oliveira (2023)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2023.